Highly porous and capacitive copper oxide nanowire/graphene hybrid carbon nanostructure for high-performance supercapacitor electrodes. (1st December 2019) - Luan, Van Hoang; Han, Jong Hun; Kang, Hyun Wook; Lee, Wonoh
Abstract: Three-dimensionally porous carbon nanostructures have been widely used in energy storage applications owing to their large specific surface areas and excellent electrical properties. In addition, copper oxide has been considered as an effective pseudocapacitive material to significantly increase the energy density. In this paper, we introduce the synergetic combination of one-dimensional copper oxide nanowires and two-dimensional graphene sheets to fabricate a highly porous and electrically conductive three-dimensional hybrid nanostructure for high-performance supercapacitor electrodes with increased capacitances. The copper oxide nanowires were synthesized by reduction of copper nitrate and sequential oxidation at a high temperature. The copper oxide nanowire/graphene hybrid three-dimensional nanostructure was obtained by a self-assembly technique through a simple hydrothermal treatment. The hybrid nanostructure had an acceptable surface area and increased thermal stability. The porous hybrid nanostructure utilized as a supercapacitor electrode provided 1.6 times higher electrochemical capacitance than that of a graphene-only nanostructure-based electrode as well as superior capacitance stability with a retention of 91.2% retention after 5, 000 charge−discharge cycles. Owing to the increased capacitance, the manufactured electrode exhibited high a specific energy density of 50.6 Wh kg −1 at a power density of 200 W kg −1, which demonstrates its potential for use in electrochemical energy storage devices.